(untitled) (Interfaces: A Journal of Medieval European Literatures, 2024)
This introductory paper sets the stage for the five contributions in this special issue, which examine the occasional literature across various linguistic traditions (Greek, Latin, and Persian) from the eleventh to seventeenth centuries. It offers reflections on the interplay between occasion, lyric, and literature, suggesting that occasional literature can be regarded as a precursor to lyric. Additionally, it explores the close relationship between occasional literature and patronage, which has significantly shaped the modern dismissive attitude toward the former.